Efficacy of adjuvant CYVADIC chemotherapy in early-stage uterine sarcomas: results of long-term follow-up. Issue 4 (1st June 2004) - Odunsi, K.; Moneke, V.; Tammela, J.; Ghamande, S.; Seago, P.; Driscoll, D.; Marchetti, D.; Baker, T.; Lele, S.
Abstract : Data on adjuvant chemotherapy in early-stage uterine sarcomas are conflicting and most often based on small patient groups with relatively short duration of follow-up. Approximately 60% of patients present with stage I disease with an overall 5-year survival of 30–50% when treated with surgery alone. This study examines the efficacy and results of long-term follow-up of a multiagent chemotherapy regimen of cyclophosphamide, vincristine, doxorubicin, and dacarbazine (CYVADIC) as adjuvant treatment for patients with stage I uterine sarcoma. Between 1982 and 1999, 24 evaluable patients with completely staged uterine sarcomas received adjuvant multiagent chemotherapy with vincristine sulfate (1mg/m 2 ) on days 1 and 4, doxorubicin (40 mg/m 2 ) and cyclophosphamide (400 mg/m 2 ) on day 2, and dacarbazine (200 mg/m 2 ) on days 1 through 4 for a total of nine monthly cycles or until recurrence of disease was documented. Survival distributions were calculated by the Kaplan–Meier method, and statistical significance was determined with the log-rank test. Factors significant on univariate analysis were analyzed in a multivariate fashion using Cox proportional hazards model. The histologic distribution of patients was 46% leiomyosarcoma, 33% mixed mullerian tumors, 13% stromal sarcomas, 4% adenosarcomas, and 4% hemangiosarcoma. The patients received 206 of a planned 216 cycles of chemotherapy. The median follow-up of the patient population was 93 months (range 11–213 months). Eight patients (33%) developed recurrent disease. The median time to recurrence was 19 months (range 7–184 months). The estimated survival for the entire group was 88, 75, and 69% at 2, 5, and 15 years, respectively. Factors that did not affect survival included age, histology, and tumor grade. Four patients required dose reductions secondary to grade 2–3 toxicities (hematologic). Grade 1 neurotoxicity was observed in six patients (25%) and grade 2 neurotoxicity in one patient (4%). Adjuvant CYVADIC chemotherapy appears to be safe and well tolerated in patients with stage I uterine sarcomas. Our data provide information on the longest duration of follow-up ever reported and suggests that CYVADIC may have a potential role in the adjuvant treatment of early-stage uterine sarcoma.